Fostering Sustainable Communities: Competencies and Training Needs for Social Organic Farming in Hungary, Greece, and Italy - Ujj, Apolka; Jancsovszka, Paulina; Ali, Mohammad Daud; Voloudakis, Dimitris; Dávid, Lóránt Dénes; Pércsi, Kinga Nagyné (Journal of Ecohumanism, 2024)
This study examines key competencies in social organic farming (SOF) as perceived by stakeholders in Hungary, Greece, and Italy, including necessary knowledge, skills, and attitudes. It also explores the educational and professional requirements for those aiming to become social organic farmers, ultimately contributing to an ideal farmer profile. Through qualitative methods, such as semi-structured interviews with stakeholders, the study identifies essential competencies and training needs for SOF. Results show that successful social organic farmers must understand organic farming principles, social work, farm economics, and possess personal skills like empathy, team-work, and effective communication. These competencies and training align with Social Capital Theory, Diffusion of Innovation Theory, and Community-Based Participatory Research, under-scoring the importance of social networks, community engagement, and innovation in advancing sustainable and inclusive agricultural practices. The study also highlights SOF’s role in supporting community well-being, enhancing sustainable food systems, and promoting both physical and mental health. Findings offer valuable insights into the limited literature on SOF, providing actionable recommendations for vocational training programs that support social organic farmers’ growth across Europe. This, in turn, fosters sustainable agriculture, circular economies, and public health, thereby strengthening community resilience and ecological stability.